2017
DOI: 10.1371/journal.pone.0170770
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Pseudomonas fluorescens MFE01 Type VI Secretion System to Biofilm Formation

Abstract: Type VI secretion systems (T6SSs) are widespread in Gram-negative bacteria, including Pseudomonas. These macromolecular machineries inject toxins directly into prokaryotic or eukaryotic prey cells. Hcp proteins are structural components of the extracellular part of this machinery. We recently reported that MFE01, an avirulent strain of Pseudomonas fluorescens, possesses at least two hcp genes, hcp1 and hcp2, encoding proteins playing important roles in interbacterial interactions. Indeed, P. fluorescens MFE01 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 76 publications
(76 reference statements)
3
56
0
Order By: Relevance
“…These findings are in alignment with the previous studies. For instance,Gallique et al (2017) reported that mutation in hcp1, hcp2, or hcp3 of P. fluorescens MFE01…”
mentioning
confidence: 99%
“…These findings are in alignment with the previous studies. For instance,Gallique et al (2017) reported that mutation in hcp1, hcp2, or hcp3 of P. fluorescens MFE01…”
mentioning
confidence: 99%
“…Biofilm formation helps bacteria contend with harsh environmental stresses in natural, clinical, and industrials setups . The T6SS has a diverse impact on biofilm formation in various bacteria; in some bacteria, it enhances biofilm formation ( Acinetobacter baumannii ; avian‐pathogenic Escherichia coli , Acidovorax citrulli ; enteroaggregative Escherichia coli ); in others, it aids in biofilm maturation ( Pseudomonas fluorescens ) or has no effect ( Vibrio alginolyticus ) . The role of T6SS in C. jejuni biofilm formation had yet to be reported, which led us to study the effect of secretory Hcp‐Cj on biofilm formation in both T6SS‐positive and ‐negative strains.…”
Section: Resultsmentioning
confidence: 99%
“…External surface of the hexamer is moderately conserved (A, B), whereas the internal surface has comparatively more variable residues (C). biofilm maturation (Pseudomonas fluorescens) or has no effect (Vibrio alginolyticus) [17,[37][38][39]. The role of T6SS in C. jejuni biofilm formation had yet to be reported, which led us to study the effect of secretory Hcp-Cj on biofilm formation in both T6SS-positive and -negative strains.…”
Section: E Coli K W Y K I W --D a G --Q E V E Y F N T K L E N V K Vmentioning
confidence: 99%
“…Even though some toxins have acquired functions which are independent of their capacity to harm competitors, such as communication between siblings (CDI) [26], contribution to biofilm formation (T6SS, CDI) [27,28], or nutrient acquisition (T6SS) [29,30], their principal purpose is interference competition. Consequently, for toxin release to be beneficial, sensitive competitors should be growing in the vicinity of the producers.…”
Section: Monitoring Competitorsmentioning
confidence: 99%